ANALISIS TINGKAT LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN UMKM DI KOTA TEGAL - Fitri Amaliyah; Hetika (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2023)
Financial literacy is the key to people achieving sustainable financial well-being and avoiding the risk of financial loss.Â  Lfinancial iteration can help usada owners in reducing risk by diversifying assets and managing debt. The study aims to determine the influence of financial literacy on basic financial knowledge, deposits and credit, investment and insurance on financial management in trading MSMEs in Tegal City. Meanwhile, the sampling technique using purposive sampling is a technique to determine research samples with certain considerations that aim to make the data obtained later more representative with a total sample of 40 MSMEs. The method of data collection in this study using a questionnaire. The hypothesis proposed, was tested statistically using WarpPLS version 7.0. The results of the study found that 1) literacy about basic financial knowledge does not affect the financial management of MSMEs, 2) Literacy about deposits and credit does not affect the financial management of MSMEs, 3) Literacy about investment has a significant positive effect on the financial management of MSMEs 4) Literacy about insurance does not have a significant effect on the financial management of MSMEs. This means that the worse the financial literacy about basic financial knowledge, deposits and credits, investment and insurance, the more high-risk financial management of MSMEs will also have a high risk. The existence of a good understanding of financial literacy can minimize risks that are not cold and provide easy financing facilities from banks.